Traveling Wave Solutions of the Nonlinear (3+1)-Dimensional Kadomtsev-Petviashvili Equation Using the Two Variables (𝐺′/𝐺,1/𝐺)-Expansion Method - E. M. E. Zayed; S. A. Hoda Ibrahim; M. A. M. Abdelaziz (Journal of Applied Mathematics)
The two variables (𝐺/𝐺,1/𝐺)-expansion method is proposed in this paper to construct new exact traveling wave solutions with parameters of the nonlinear (3+1)-dimensional Kadomtsev-Petviashvili equation. This method can be considered as an extension of the basic (𝐺/𝐺)-expansion method obtained recently by Wang et al. When the parameters are replaced by special values, the well-known solitary wave solutions and the trigonometric periodic solutions of this equation were rediscovered from the traveling waves.